Intracranial massive subdural haematoma: a potentially serious consequence of diagnostic lumbar puncture - Manorenj, Sandhya; Kandukuri, Suma; P. S., Muralikrishna; Barla, Sudhakar (International Journal of Research in Medical Sciences, 2017)
Intracranial subdural haematoma (SDH) is an exceptionally rare complication of lumbar puncture (LP) and cerebrospinal fluid (CSF) drainage. Post LP headache mostly has a benign course, but it can also be a manifestation of a potentially life-threatening complication such as SDH. Only a few cases has been reported in literature. We report a case of massive intracranial SDH in a young male following LP and CSF drainage.